DAMPAK PENGGUNAAN MEDIA SOSIAL PADA HASIL BELAJAR MATEMATIKA SISWA SMP NEGERI 1 PUSOMAEN - Carina Olita Selin Tulandi; Sylvia J. A Sumarauw; Vivian E. Regar (EDUCATIONAL JOURNAL : General and Specific Research, 2022)
This study aims to determine the impact of the use of social media, especially YouTube on the mathematics learning outcomes of SMP Negeri 1 Pusomaen students. The social media youtube is the largest video presenter in the world today which contains all types of videos. Most of the students of SMP Negeri 1 Pusomen admitted that they prefer to use YouTube social media when they are at school rather than studying, besides that mathematics subjects are less attractive to students because they are considered very boring, making students rarely study when they are at home. Mathematics learning that is less attractive to students and excessive use of social media during class hours results in student learning outcomes that are still below the KKM. The type of research used is descriptive qualitative. Data collection techniques are observation, questionnaires/questionnaires, and interviews. Data analysis techniques in the form of data reduction, data presentation, and data verification. The results of the study at the time of observation showed that students had various reasons for using YouTube social media, but almost all of the students who were sampled very often used this social media anywhere and anytime, including at school when learning took place. The frequent use of social media by students has an impact on students' mathematics learning outcomes. The distributed questionnaire score data also shows that students really like YouTube social media with a percentage of 56% in the response aspect, and 54% in the reaction aspect. At the time of the research, the researcher tried to find out more about the impact of using YouTube social media on student learning outcomes, by making YouTube social media a learning resource, and it was found that students were very enthusiastic during the learning process and the learning outcomes obtained were 88 out of 100 students. have finished studying. This makes the use of YouTube social media a positive impact if used properly. So, the conclusion that can be drawn from the implementation of this research is that the use of appropriate social media has a positive impact on the mathematics learning outcomes of SMP Negeri 1 Pusomaen students and has a negative impact on student learning outcomes if it is used excessively and not as a learning resource.